Safety Profile of Abelmoschus Manihot (L.) Medik Ethanol Leaf Extract: Acute Toxicity Study in Animal Models - Magfira B. Pantua; Viani Anggi; Indah Kurnia Utami; Yasinta Rakanita (Postgraduate, University of Mataram, 2024)
Abelmoschus Manihot (L.) Medik, commonly known as Abelmoschus manihot, is a traditional medicinal plant from Palu, Central Sulawesi, Indonesia, widely utilized for its potential health benefits. This research aims to evaluate the acute toxicity of ethanol extract from Abelmoschus manihot leaves, focusing on determining the lethal dose (LD50) in rats. The study involved extracts being administered at a range of doses of 500 mg/kg, 1000 mg/ kg, and 2000 mg/Kg of body weight (BB) in a rat population. Rats were observed for 24 hours to look for signs of toxicity and death. The LD50 value, which determines the dose required to cause death in 50% of the test population, is calculated based on the results. This research provides insights into the safety profile of ethanol extract from Abelmoschus manihot leaves and contributes to understanding its potential risks when used in traditional medicine. No significant deaths were observed at lower doses, but higher doses resulted in observable toxic effects, indicating the need for careful dosing in therapeutic applications. The results show that although Abelmoschus Manihot did not exhibit acute toxic effects on rats at doses of 500 mg/kg, 1000 mg/kg, and 2000 mg/kg body weight. No significant deaths or severe toxic symptoms were observed during the 24-hour observation period up to the 14-day observation, and there were no differences in the body weight of the rats during the 14-day observation